The Effect of L-arginine in the Ventral Tegmenta Area on the Improving Effect of Nicotine on Memory - Shahin M.S; Piri M; Zarrindast M.R (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2012)
Background and Objectives: Nitric oxide synthesis has been detected in ventral tegmental area, which is a key brain region that seems to mediate behavioral effect of morphine and nicotine. In the present study, the effects of L-arginine, a nitric oxide precursor, in the ventral tegmental area in nicotine’s effect on morphine-induced amnesia has been investigated.Methods: This study was done experimentally on 250 male rats. Rats were anesthetized with intra-peritoneal injection of ketamine hydrochloride, plus xylazine and then placed in a stereotaxic apparatus. Two stainless-steel cannuale were placed in the ventral tegmental area. The behavioral testing was started in inhibitory avoidance task, and the step-through latency for entering into the dark compartment was measured for the assessment of memory retention. One-side analysis of variance (ANOVA) and Tukey test were used to evaluate the statistical significance between experimental groups. A difference of p<0.05 was considered statistically significant.Results: Post-training injection of morphine (5 and 7.5mg/kg) decreased the memory retrieval. Injection of nicotine or L-arginine before test by itself has no effect on memory retrieval. On the other hand, pre-test administration of morphine (7.5mg/kg), nicotine (0.5 and 1mg/kg), L-arginine or ineffective doses of L-arginine plus non-effective dose of nicotine restored memory impairment induced by post-training injection of morphine.Conclusion: The finding of the study indicate that nitric oxide system of the ventral tegmental area may play an important role in the improving effect of nicotine on the morphine-induced amnesia.